The Bright Side of Supplier Encroachment - Arya, Anil; Mittendorf, Brian; Sappington, David E. M. (Marketing Science, 2007)
The common wisdom is that a retailer suffers when its wholesale supplier encroaches on the retailer's operations by selling directly to final consumers. We demonstrate that the retailer can benefit from encroachment even when encroachment admits no synergies and does not facilitate product differentiation or price discrimination. The retailer benefits because encroachment induces the encroaching supplier to reduce the wholesale price in order not to diminish unduly the retailer's demand for the manufacturer's wholesale product. The lower wholesale price and increased downstream competition mitigate double marginalization problems and promote efficiency gains that can secure Pareto improvements.